Case report: Sodium-glucose cotransporter 2 inhibitors induce left ventricular reverse remodeling in anthracycline-related cardiac dysfunction—a case series - Giangiacomi, Francesco; Faggiano, Andrea; Cardinale, Daniela; Rossi, Francesca Gaia; Pollina, Alberto; Gherbesi, Elisa; Gnan, Eleonora; Carugo, Stefano; Vicenzi, Marco (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To describe the efficacy and safety of sodium-glucose cotransporter 2 inhibitors as a specific treatment for anthracycline-related cardiac dysfunction in a small real-world population. Methods: Seven patients with anthracycline-related cardiac dysfunction were clinically and echocardiographically evaluated before and after the introduction of sodium-glucose cotransporter 2 inhibitors. Results: After a median period of 24 weeks with uninterrupted sodium-glucose cotransporter 2 inhibitors treatment, a significant clinical improvement was observed with at least one New York Heart Association Functional Class (NHYA FC) improvement in all patients (median NYHA FC: I vs III, p<0.010). A noteworthy left ventricular reserve remodeling (median left ventricular end diastolic volume indexed: 53 vs 82.5 ml/m2, p=0.018; median left ventricular ejection fraction: 50% vs 40%, p=0.17) was also observed. Sodium-glucose cotransporter 2 inhibitors therapy was well tolerated by every patients; no cases of discontinuation or relevant side effects were observed. Conclusion: Sodium-glucose cotransporter 2 inhibitors induce a significant clinical improvement and left ventricular reserve remodeling in patients affected by anthracycline-related cardiac dysfunction.